WHAT ARE THE CONDITIONS FOR GENERATING POSITIVE IMPACTS ON THE LIVELIHOOD OF PES PARTICIPANTS IN IMPLEMENTING THE PES SCHEME? A COMPARISON BETWEEN PES FOR WATERSHEDS IN INDONESIA AND TANZANIA - Hashilah, Fathia; Waluyo, Septian Agung (UI Scholars Hub, 2022)
Many scholars perceive that Payment for Environmental Services (PES) will automatically benefit environmental conditions and the livelihood of the environmental services (ES) providers. Some contextual conditions might create a positive impact on the livelihood of ES providers. This paper aims to obtain the contextual needs of PES implementation that positively affect the livelihood of ES providers. Comparing two studies of the PES scheme in Indonesia and Tanzania, there are four general conditions for achieving benefits for ES providers from implementing PES. First, the PES scheme should be well-designed. Second, potential PES participants need to have a solid institutional condition. Third, the intermediaries of the PES scheme should be skilful and knowledgeable. Fourth, the land right should be well recognized, whether individual, collective or government-owned.